Chapter Signorie in un'area di strada. La Valsugana nel XIV secolo - Franceschini, Italo (Reti Medievali E-Book, 2023)
The Valsugana, crossed by the river Brenta, is a perfect example of a 'road area'. The seigniorial families installed in this territory juggled between the bishop of Feltre and the prince-bishop of Trento, not without a certain amount of military pressure from the city lords of the Veneto region (Scaligeri, Carraresi). During the 15th century the authority of the Habsburgs asserted itself in Valsugana.